OUTING CLASS DALAM PERSPEKTIF PENDIDIKAN MODERN: KAJIAN LITERATUR TENTANG EFEKTIVITASNYA BAGI SISWA SEKOLAH DASAR - Dendi Nur Ahmad; Alfan Nurngain (DAS Institute, 2026)
Modern 21stcentury education requires innovative learning approaches that go beyond the mere transfer of knowledge and emphasize the development of critical thinking, creativity, communication, and collaboration skills. One relevant strategy is the outing class, a learning activity conducted outside the classroom that utilizes the environment as a learning resource. This article aims to examine the effectiveness of outing class in enhancing motivation, learning outcomes, and socioemotional skills of elementary school students through a literature review. The study employs a qualitative descriptive method by analyzing seven articles published between 2024 and 2025, sourced from academic databases such as Scopus, Science Direct, Springer, Google Scholar, DOAJ, and Garuda. The analysis was carried out through theme identification, categorization of key issues, and inductive conclusions to reveal patterns and research gaps. Findings indicate that outing class increases student engagement, strengthens contextual understanding, and bridges theory with realworld practice. Empirical evidence highlights its effectiveness in supporting the implementation of the Kurikulum Merdeka, improving learning motivation, and fostering creativity and writing skills. Moreover, outing class plays a crucial role in cultivating 21stcentury competencies by providing direct experiences that encourage students to think critically, collaborate, and communicate actively. Nevertheless, its implementation faces challenges such as limited funding, unpredictable weather, large class sizes, and the need for risk management. Recommended strategies include careful planning, small group division, intensive supervision, and involvement of parents and the community. Overall, outing class proves to be a relevant contextual learning method that supports modern education while contributing significantly to student motivation, achievement, and social skills in elementary schools.